2017
DOI: 10.1021/acs.langmuir.7b02725
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Ester Sulfonate at the Air–Water Interface: Can Limitations in the Application of the Gibbs Equation be Overcome by Computer Purification?

Abstract: We describe a new laboratory synthesis of the α-methyl ester sulfonates, based on direct sulfonation of the methyl ester by SO 3 introduced from the vapour phase. This was used to synthesize a chain deuterated sample of αC 14 MES, which was then used to measure the surface excess of αC 14 MES directly at the air/water interface over a wide range of concentration using neutron reflection. The adsorption isotherm could be fitted to an empirical equation close to a Langmuir isotherm and gave a limiting surface ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…For nonionic and zwitterionic surfactants, a value of 1 for the pre-factor has been confirmed [19,20], and for 1:1 ionic surfactants, in the absence of extra electrolyte, m = 2 has been confirmed [18]. Recently, it has been shown that traces of multivalent ionic impurities can lead to changes in this prefactor, therefore leading to problems employing the Gibbs adsorption isotherm [21]. In this study, a prefactor of 1 has been used for the non-ionic and zwitterionic surfactants, and a prefactor of 2 has been used for the anionic surfactants, following literature [18][19][20].…”
Section: Surface Tension Measurementsmentioning
confidence: 92%
“…For nonionic and zwitterionic surfactants, a value of 1 for the pre-factor has been confirmed [19,20], and for 1:1 ionic surfactants, in the absence of extra electrolyte, m = 2 has been confirmed [18]. Recently, it has been shown that traces of multivalent ionic impurities can lead to changes in this prefactor, therefore leading to problems employing the Gibbs adsorption isotherm [21]. In this study, a prefactor of 1 has been used for the non-ionic and zwitterionic surfactants, and a prefactor of 2 has been used for the anionic surfactants, following literature [18][19][20].…”
Section: Surface Tension Measurementsmentioning
confidence: 92%
“…30 it has been shown that traces of multivalent ionic impurities can lead to changes in this prefactor, therefore leading to problems employing the Gibbs adsorption isotherm. 33 In this study, only anionic surfactants are being studied and therefore a prefactor of 2 has been used in all calculations as indicated in the literature. [30][31][32]…”
Section: Surface Tensionmentioning
confidence: 99%
“…The physicochemical properties of α‐MES have been investigated (Danov et al, ; Ohbu et al, ; Patil et al, ; Stirton et al, ; Wong et al, ; Xu et al, ), with its superiority under hard water conditions. However, there are not many references on its cleaning performance against the dominant workhorse in the Home Care product—linear alkylbenzene sulfonate (LAS).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the binding energy of the Ca 2+ ions (2.39 КT) to the headgroup of α-MES is smaller than that of Na + (2.91 КT), which helps explain the superiority of α-MES under challenging conditions. The physicochemical properties of α-MES have been investigated (Danov et al, 2015;Ohbu et al, 1998;Patil et al, 2004;Stirton et al, 1962;Wong et al, 2012;Xu et al, 2017), with its superiority under hard water conditions. However, there are not many references on its cleaning performance against the dominant workhorse in the Home Care product-linear alkylbenzene sulfonate (LAS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation